2020
DOI: 10.3390/v12020242
|View full text |Cite
|
Sign up to set email alerts
|

Measles Vaccines Designed for Enhanced CD8+ T Cell Activation

Abstract: Priming and activation of CD8 + T cell responses is crucial to achieve anti-viral and anti-tumor immunity. Live attenuated measles vaccine strains have been used successfully for immunization for decades and are currently investigated in trials of oncolytic virotherapy. The available reverse genetics systems allow for insertion of additional genes, including heterologous antigens. Here, we designed recombinant measles vaccine vectors for priming and activation of antigen-specific CD8 + T cells. For proof-of-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 71 publications
1
7
0
1
Order By: Relevance
“…The intensity of the innate and adaptive immune response is closely related to the occurrence, development and prognosis of COVID-19 [9]. Lymphocytes are the main executors of adaptive immune functions [7,8]. Previous studies have shown that the severity of COVID-19 may be related to PLC levels [12,[15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of the innate and adaptive immune response is closely related to the occurrence, development and prognosis of COVID-19 [9]. Lymphocytes are the main executors of adaptive immune functions [7,8]. Previous studies have shown that the severity of COVID-19 may be related to PLC levels [12,[15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytes produced by lymphoid organs are the smallest white blood cells (WBCs) and are important cellular components of the immune response in the body. They are also the main executor of immune functions of the lymphatic system and the front-line defense against external pathogens in the body [ 7 , 8 ]. In addition to the pathogenicity of the virus itself, the inflammatory response of the host is a key factor in SARS-CoV-2-induced lung injury [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The epitope variants are either secreted or targeted to the proteasome. Using these MeV vectors, activation and dendritic cell-mediated priming of cognate T cells was demonstrated ex vivo [ 115 ].…”
Section: Immunovirotherapymentioning
confidence: 99%
“…Этот подход использован при разработке вакцин против множества патогенов, включая вирусы гепатита В, Денге, ВИЧ, коронавирусы SARS и MERS, малярийный плазмодий. В ряде работ показана способность вектора индуцировать устойчивый В-и Т-клеточный ответ [46].…”
Section: рекомбинантные вакцины на основе вирусаunclassified